Facile, economical and environment-friendly synthesis process of porous N-doped carbon/SiOx composite from rice husks as high-property anode for Li-ion batteries. (20th February 2020) - Cui, Jinlong; Zhang, Haibang; Liu, Yunying; Li, Shaohui; He, Wenxiu; Hu, Jiangliang; Sun, Juncai
Abstract: To enhance electrochemical properties of C/SiOx composite for business application, N-doped carbon/SiOx composite has been successfully fabricated using rice husks as the raw material of both C and Si sources and urea as N source via an environmentally friendly and economically viable strategy. The obtained N@C/SiOx composite exhibits a porous irregular particle morphology with a high specific surface area. SiOx particles are uniformly dispersed in N-doped C skeleton. As an anode material for Li-ion batteries, the porous structure, N doping and high reduction degree of SiO2 endow N@C/SiOx electrodes with an outstanding reversible capacity up to 1018.5 mAh/g at 0.1 A/g and a remarkable initial coulombic efficiency of 72.2%, which is larger than that of carbonized rice husks (45.7%). Even if the current density rises to 1.0 A/g, the reversible specific capacity can maintain at 623.3 mAh/g with a capacity degradation of merely 4.0% after 1000 cycles. Graphical abstract: Image 1 Highlights: SiOx particles are uniformly dispersed in N-doped C skeleton in N@C/SiOx composite. N-doped C skeleton effectively enhance electronic conductivity of C/SiOx composite. The presence of N can increase specific capacity and initial CE of C/SiOx electrode. Zero emissions and zero pollution are achieved in the entire production process.